Ghosts in a Wilderness: Problems and Priorities of Faculty at Mid-Career and Mid-Life - Karpiak, Irene E. (Canadian Journal of Higher Education, 1996)
This article explores the experiences of mid-career, older faculty members in higher education through a qualitative study of 20 associate professors (15 men and 5 women) between the ages of 41 and 59 at a Canadian university. The study was undertaken to explore how university faculty experience the mid-career and mid-life period in their academic and community work, their personal and family relationships, and their sense of self. The findings focus on a variety of issues revealed in this sample group: the undervalue of teaching as a vocation, noncaring university administrators, rejection in career progression, external personal relationships, impediments to research, failing health, adapting to change, and the question of self-knowledge. While acknowledging several limitations of the study, the perspective of adult development theory points to the potential for greater integration of personality on the part of faculty members, and for its recognition on the part of administrators in fostering a more humanizing, responsive, and caring environment for the conduct of teaching and research. The recognition of significant differences between younger and older faculty, and how the genuine problems facing the latter group may be addressed, will contribute to enhancing the quality of university life generally.